A evolução da identidade organizacional da área de ensino da Fundação João Pinheiro - Raphaella Aragão Vieira (2020)
ABSTRACT The objective of this dissertation was to identify the evolution of organizational identity (IO) through the classification of the most significant events in the life cycle of an organization. As the object of research, the teaching area of the João Pinheiro Foundation (FJP) was chosen, from 1969 to 2018 - a public organization renowned in the State of Minas Gerais that operates in the areas of teaching and research. The lack of studies in the public sector and the lack of evolutionary analyzes of IO were the main motivators for choosing the theme of this research. To achieve the proposed objectives, a qualitative, descriptive and explanatory research was carried out, using the case study method, from a longitudinal perspective. As methodological procedures, documentary survey and analysis were used, in addition to interviews with former FJP employees who worked and work in teaching activities. The research presents as a result a methodology for analyzing the evolution of an organization's identity through the classification of its most significant events according to the dimensions of the IO: centrality, distinctiveness and durability. This research contributes to the literature on IO via the presentation of a new model to study the evolution of the construct and still allows the FJP to know, from a historical perspective, the identity transformations of its teaching area.